The Development of a New Model of Educational Leadership: Leadership for Teacher Flourishing - Granville-Chapman, K; Lee, MT; Ritchie-Dunham, J (Springer, 2024)
This paper contributes to a broader movement in which the telos of leadership is flourishing, and the primary role of a leader is to promote the flourishing of their team members through creating a loving environment. In support of this, we propose a new perspective on, and associated model, of educational leadership: ‘leadership for teacher flourishing’ (LFTF). This model was developed through a literature review and a mixed methods research project across 78 British schools with collaborative and participatory elements which asked how school leaders could improve the flourishing of teachers. The quantitative and qualitative findings suggested that key factors in enabling teachers to flourish, and therefore incorporated into the model ‘LFTF’, were positive relationships; opportunities for growth; positive impact on subjective wellbeing; and increasing teachers’ sense of meaning at work. The ways leaders could impact these factors were reported as: being supportive and compassionate; being trustworthy; giving teachers autonomy; enabling teachers to grow; being appreciative and focusing on strengths; and enabling teachers to do meaningful work. It was also found that not only leaders could influence flourishing; teachers with no formal leadership role could also positively impact teacher flourishing. It is suggested that virtuous dispositions in leaders are required to ensure they are consistent in acting in ways that promote flourishing. We argue that this integration of virtue and a desire to promote flourishing is properly understood as love. The participatory and collaborative phase of the research showed that teachers wanted autonomy in deciding what would help them to flourish. The conclusion sets out the implications of this research for policy on the training and selection of school leaders, to improve not only the flourishing of teachers, but also pupils and communities.